Gender Differences in Mental Health Disorder and Substance Abuse of Chinese International College Students During the COVID-19 Pandemic - Li, Mingsheng; Su, Heng; Liao, Zhengluan; Qiu, Yaju; Chen, Yan; Zhu, Junpeng; Pei, Yangliu; Jin, Piaopiao; Xu, Jiaxi; Qi, Chang (Frontiers in Psychiatry, 2021)
Introduction: The outbreak of Coronavirus disease has negatively impacted college students' mental health across the world. In addition, substance abuse also is trouble among these students. This study aims to find the gender difference in Chinese international college students' mental health and substance abuse during the COVID-19 pandemic. Method: We conducted an online survey using PHQ-9, GAD-7, and several questions related to substance abuse frequency, self-injury, and suicidal thoughts. 535 male and 475 female Chinese international college students were recruited during the epidemic whose ages ranged from 18-23 years old. We utilized t-test and binary logistic regression in our study to find out the difference and statistical significance between substance abuse issues and mental health problems across gender. Results: Both male and female Chinse international college students had a statistically significant with self-injury ideas and behaviors (t = -2.21, P < 0.05). Furthermore, the male college students with anxiety problems had a positive statistically significant with medicine (OR = 3.47, 95%CI = 1.45 – 8.30, P < 0.01) and a negative statistically significant with drinks (OR = 0.23, 95%CI = 0.08 – 0.65, P < 0.01). While for female college students with anxiety problem, they had a positive statistically significant with medicine (OR = 4.88, 95%CI = 1.53 – 15.57, P < 0.01), drugs (OR = 4.48, 95%CI = 1.41 – 14.25, P < 0.05) and cigarettes (OR = 6.63, 95%CI = 1.95 – 22.57, P < 0.01) and a negative statistically significant with drinks (OR = 0.18, 95%CI = -0.05 - 0.65, P < 0.01). Conclusion: This is the first cross-sectional study focusing on the Chinese international college students' mental health and substance abuse problems during the COVID-19. We found that Chinese international college students' mental health and substance abuse situation has been negatively influenced during this period. In addition, the self-injury ideas and behaviors also showed a high tendency for these students. The findings of our study also highlight the need to find more interventions and preventions to solve the different mental health and substance abuse problems for college students, especially for female Chinese international college students.